Odpowiedzi

2010-03-30T21:25:03+02:00
X+3y-12=0
2x-y-3=0

x+3y=12
2x-y=3 /*3

x+3y=12
6x-3y=9

7x=21 /:7
x=3

3+3y=12
3y=9 /:3

y=3
x=3

---------------------

2x-y-5=0
3x=y-6

2x-y=5 /*-3
3x-y=-6 /*2

-6x+3y=-15
6x-2y=-12

y=-3

3x+3=-6
3x=-3

x=-1
y=-3

--------------------------

x+4y-14=0
3x-y=20

x+4y=14
3x-y=20 /*4

x+4y=14
12x-4y=80

13x=94
x=7,23

21,69-y=20
y=-1,69

y=-1,69
x=7,23

2010-03-30T21:27:20+02:00
A)x+3y-12=0
2x-y-3=0


x+3y=12
2x-y=3

-2x-6y=-24
2x-y=3

-7y=-21
y=3

x+3y=12
x+9=12
x=3


b)2x-y-5=0
3x=y-6

2x-y=5
3x-y=-6

-2x+y=-5
3x-y=-6

x=-11

3x=y-6
-33=y-6
-y=27
y=-27



c)x+4y-14=0
3x-y=20

x+4y=14
3x-y=20

-3x-12y=-42
3x-y=20

-13y=-22
y=22/13

3x-y=20
3x-22/13=20
3x=20+22/13
3x=282/13
x=282/39